Simulation stress and finite element analysis based of Suzuki FXR 150cc motorcycle chassis - Mohd Khairudin, Yahya (2007)
Simulation stress and finite element analysis of Suzuki FXR 150cc motorcycle chassis is the main focus of this project. This research was carried out to investigate the most critical point or joining of a chassis part location of the vehicle to enhance more comfort and safe ride. The information that has been used is based on the previous study about the frame. The approximation measurement of the model of Suzuki FXR 150cc motorcycle chassis had been done. The analysis is done either by experimental or finite element analysis. The result from the analysis is an approximation of the component failure. In the mean time, the software development is improving in this few decades. Most of the new software makes the analysis and designing easier to understand. This project aim to determine the location and stress concentration of Suzuki FXR 150cc motorcycle chassis with the aim of frame as the major data contribution. Solidworks and Algor software is used for determination of stress concentration on the component and the system.